Understanding the Role of Institutional Pressure in Organisational Change: The Case Study of Chinese State-Owned Enterprises - Zhou, Zhike (2006)
Chinese economy has been undertaking a boom since the government launched the famous "reform and opening up" policies in 1979. The reformation of Chinese economy concentrates not only on the transformation from planned economy to market-based economy, but also on the transition of State-Owned-Enterprises (SOEs).